Effect on cholesterol remnants and residual lipid risk with PCSK9 inhibitors: the LIPID-REAL Registry. (3rd October 2022) - Fernandez Del Olmo, R; Cordero, A; Cortez Quiroga, G; Romero-Menor, C; Facila, L; Rondan, J; Bello Mora, M C; Sandin, M; Valle, A; Freixa, R; Blanch, P; Baneras, J; et al.
Abstract: Background: Monoclonal antibodies that inhibit the proprotein convertase subtilisin/kexin type 9 (PCSK9) reduce low-density lipoprotein cholesterol (LDLc) by 55%, regardless of baseline treatments. Nonetheless, the effect of other lipid parameters, as cholesterol remnants or, the so-called residual lipid risk, are unknown. Methods: Multicenter and retrospective registry of patients treated with PCSK9 inhibitors from 14 different hospitals from Spain. Before and on-treatment lipid parameters were recorded. Cholesterol remnants were calculated by the equation: total cholesterol minus LDLc minus HDLc and values ≥30 were considered high. Residual lipid risk was estimated by 1) the estimation of LDL particle size, by the triglycerides/HDLc ratio (TG/HDL) and values <2 were assumed as low and dense LDL particles; 2) total cholesterol/HDLc (TC/HDL) and values >3 were considered high; and; 3) the triglycerides-to-glucose (TG/Gluc) index, obtained as the natural logarithm of (triglycerides * glucose/2) Results: A total of 652 patients were analyzed, mean age 60.0 (10.5) years and 161 (24.69%) women. Baseline LDLc was 149.2 (49.9) mg/dl, cholesterol remnants 29.9 (20.3) mg/dl, TG/HDL 3.9 (4.1), TC/HDL 4.9 (1.9) and TG/Gluc index 8.9 (0.7). Most patients (92.3%) were on statins; 54.8% with ezetimibe, 8.5% with fibrates. Evolocumab was initiated in 318 (56.6%) patients; 229 (40.7%) alirocumab 75 mg and 15 (2.7%) alirocumab 150 mg. Median time to second blood determination were 187.5 (IQR 101–242) days. Mean on-treatment LDLc was 67.46 (45.78) mg/dl what represented a 55% reduction. As shown in the figure, significant reduction in cholesterol remnants (p=0.017), TG/HDL ratio (p=0.020), TC/HDL ratio (p<0.001) and TG/Gluc index (p<0.001). The percentage of patients with remnants >30 mg/dl decreased: 34.62% to 30.07 (p<0.01). Significant reductions were also observed in the percentage of patients with TG/HDL >2 (71.25% to 61.98%; p<0.01) or TC/HDL >3 (94.28% to 38.97%; p<0.01) Conclusions: This multicenter and retrospective registry of real-world patients treated with PCSK9 inhibitors demonstrates a positive effect on cholesterol remnants and lipid-residual risk beyond LDLc reductions. Funding Acknowledgement: Type of funding sources: None.